Agriculture Productivity Growth in Brazil : Recent Trends and Future Prospects - Arias, Diego (World Bank, Washington, DC, 2019)
The industrialization process in Brazil begun in the 1960s and intensified in the 1970s, however the expected productivity growth of the overall economy and structural transformation did not happen. Since the end of the 1970s, the Brazilian labor productivity has been lower than many similar economies, currently representing around one fourth of the average labor productivity in Organization for Economic Co-operation and Development (OECD) countries. One of the reasons for the weak productivity performance of the Brazilian economy in the past decades has been the manufacturing sector. Between 2000-2013, agriculture productivity rose by 105.6 percent, compared to only 11.7 percent in the services sector and -5.5 percent in the manufacturing sector. This report will focus mainly on policies related to key production factors (such as human, physical, and natural capital) and agriculture policies. The motivation for this report is to explore the evolution and source of the strong agriculture productivity growth that has occurred in Brazil in recent decades, identifying opportunities and challenges for future development of the sector. The goal is to look for opportunities to accelerate agriculture productivity growth, to have an increased impact on sector growth, jobs, environmental sustainability, and poverty reduction, as well as potentially to shed light on lessons that can contribute to efforts to boost productivity in other sectors within Brazil. The report is divided into five sections. Section one give introduction; section two describes the evolution and sources of agriculture productivity growth in recent years; section three evaluates the contributions of different factors of production, such as natural, human, and physical capital; section four explores the opportunities for further maximizing agriculture growth in Brazil through increases in productivity; and section five presents conclusions and policy recommendations on how to further maximize agriculture productivity in Brazil while having positive social (poverty reduction and jobs) and environmental impacts.